Global Trends in Sharia Audit Practice: An In-depth Bibliometric Exploration - Syaputri, Anastasya Dinda; Sigid, Sigid Eko Pramono (SMART Insight, 2024)
The surge in publications focused on Sharia Audit Practice from 2011 to 2023 has been comprehensively explored through bibliometric analysis on the Dimension.ai platform. The research aims to identify prevalent topics and writing styles among authors in this sector. Using the search term